ADVERSE EFFECTS OF LONG-TERM CORTICOSTEROID THERAPY OF NEPHROTIC SYNDROME IN CHILDREN - T. L. Nastausheva; O. A. Zhdanova; G. A. Batishcheva; T. G. Zvyagina (Педиатрическая фармакология)
Background: Long-term corticosteroid therapy in children leads to plenty of adverse effects with negative influence on health. Objective: analysis of adverse effects of corticosteroids in children with steroid-sensitive  nephrotic syndrome and development of recommendations of their early detection.Methods: A retrospective study is conducted on children with this syndrome aged 3–18 who applied to Voronezh Regional Children’s Clinical Hospital № 1 in 2011–2014.  Complications  of corticosteroid  therapy revealed during clinical examination of children were taken into account. Data on 118 healthy children examined in 2012–2014 were used to calculate integral index.Results: The study analyses treatment results of 18 children who received glucocorticosteroids  during 6 months before hospitalization and 13 children who were withdrawn from glucocorticosteroids  for 6 months or more before hospitalization. Among adverse reactions in group 1 there prevailed overweight/obesity  (78%), reactive pancreatitis (72%), leukemoid reactions (67%), liver damage (61%), Cushingoid syndrome (44%), chronic gastroduodenitis  (33%). Hyperglycemia (11%), hypertension (6%) and infection (6%) were less common. In group 2 only 2 (15%) patients had chronic gastroduodenitis,  other complications were not documented. Indices that change in children with nephrotic syndrome during corticosteroid treatment (body mass index, blood serum glucose and amylase) were measured by a single scale using modifications coefficients. Average value of the coefficients is suggested to be a new diagnostic criterion (metabolic reaction index) which allows to reveal corticosteroid adverse effects before any clinical manifestations.Conclusion: Most adverse reactions of glucocorticosteroids are short-term and continue after 6 months in a small number of patients.